Cholesterol efflux capacity and its association with prevalent metabolic syndrome in a multi-ethnic population (Dallas Heart Study). - Oludamilola Akinmolayemi (Public Library of Science (PLoS), 2021)
Metabolic syndrome (MetS) is characterized by adiposity and atherogenic dyslipidemia consisting of elevated triglyceride and decreased high density lipoprotein cholesterol (HDL-C) levels however, cholesterol concentration alone does not reflect HDL functionality. Cholesterol efflux capacity (CEC) captures a key anti-atherosclerotic function of HDL; studies linking CEC to MetS have yielded inconsistent findings and lacked racial/ethnic diversity. The aim of this study was to evaluate the association between CEC and MetS in a large multi-ethnic population utilizing two different CEC assays interrogating overlapping but distinct reverse cholesterol transport pathways. A cross-sectional study was performed using the Dallas Heart Study cohort and cholesterol efflux was measured with radiolabeled and fluorescent cholesterol assays. The relationship between CEC and MetS was assessed using multivariable regression analyses. A total of 2241 participants were included (mean age was 50 years; 38% men and 53% Blacks). CEC was independently and inversely associated with MetS irrespective of efflux assay (CEC-radiolabeled, adjusted OR 0·71 [95% CI 0·65-0·80]. CEC-fluorescent, adjusted OR 0·85 [95% CI 0·77-0·94]). Both CEC measures were inversely associated with waist circumference and directly associated with HDL-C but not with other MetS components. There was an interaction by sex but not by race such that the inverse associations between CEC and MetS were somewhat attenuated in men (OR 0·86, 95%CI 0·74-1·01). In this large multi-ethnic cohort, impaired CEC is linked to MetS irrespective of efflux assay and race/ethnicity but less so among men. Future studies are needed to assess whether CEC mediates the atherosclerotic cardiovascular disease risk of MetS.